Model predictive control system based on direct yaw moment control for 4WID self-steering agriculture vehicle - Liu, Hui; Yan, Shicheng; Shen, Yue; Li, Chiheng; Zhang, Yafei; Hussain, Fida (International Journal of Agricultural and Biological Engineering, 2021)
A model predictive control (MPC) approach based on direct yaw moment control (DYC) was proposed to realize the self-steering drive for a newly autonomous four-wheel independent-drive (4WID) agricultural electric vehicle. The front axle and rear axle of the vehicle chassis could rotate simultaneously around their respective center points and cut the turning radius in half at most through specific mechanical chassis structure design and four-wheel electrical drive. It had great potential to reduce wheel traffic damage to field crops if two rear electrical drive wheels can be controlled to follow wheel tracks of two front wheels during self-steering operation. Therefore, firstly, a two-degree-freedom dynamics model presenting this agricultural electric vehicle was constructed. Then, an MPC controller combined with DYC was applied to arrange torques from four wheels to match desired turning angles, direct yaw moments and travel speeds. The simulation results existed small steady error of steering angles below 0.22% as they were set at 5°, followed with yaw moment under 0.17% and velocity less than 1%. Finally, according to experiment results, the vehicle successfully made a working turning radius of 9.1 m with maximum error of 0.55% when desired steering angles were 5° at the speed of 1 m/s and a minimum turning radius of 1.51 m with maximum error of 6.6% when steering angles were 30° at the speed of 0.5 m/s. It verified that the 4WID agricultural electric vehicle could drive autonomously and steady with small self-steering angle error under the proposed control system and has a feasibility to reduce wheel traffic damage during driving and operation. Keywords: agriculture mechanization, 4WID electric vehicle, self-steering, model predictive control DOI: 10.25165/j.ijabe.20211402.5283 Citation: Liu H, Yan S C, Shen Y, Li C H, Zhang Y F, Hussain F. Model predictive control system based on direct yaw moment control for 4WID self-steering agriculture vehicle. Int J Agric & Biol Eng, 2021; 14(2): 175–181.